(untitled) (SAARC Journal of Agriculture, 2019)
The present study is an attempt to assess the existing agronomic practices of black gram cultivation, its impact on farmers livelihood and constraints of black gram production and marketing. Primary data from 85 farmers were collected during February to March 2016 through face to face interviews. Descriptive statistics and Garret ranking method were used to analyze the data. The majority of the farmers had sown seeds during the last week of September to first week of October. The average seed rate was found to be 19.36 kg per hectare which indicated that all farm households used below recommended dose of seeds (35-40 kg/ha). The average yield of black gram was found higher than the national average. The average net income was observed to be Tk. 26990 and Tk. 19845 in Sherpur and Jamalpur respectively. The average gross margin was observed to be Tk. 37629 on total variable cost basis. It was also found that average returns to labour was Tk. 1000/man-day in Sherpur and Tk. 692/man-day in Jamalpur district respectively. It was also observed that all kinds of livelihood assets of the selected farmers increased significantly through black gram farming. The results revealed that the main constraints faced by black gram grower were lack of irrigation facility, non availability of HYV seeds, low output price, labour scarcity, lack of knowledge about improved varieties with their production technology, excessive rainfall after flowering and weak research-extension farmers linkage etc. Farmers also faced some marketing related problems such as limited buyers, price instability, lack of storage facilities and high market toll. Farmers cultivated black gram because of higher yield, higher income, and easy growing. SAARC J. Agri., 16(2): 83-96 (2018)